Peningkatan Hasil Belajar Tematik Terpadu dengan Model Problem Based Learning di Kelas V SD - Idola Nurhidayah; Yalvema Miaz (Universitas Negeri Padang, 2020)
The study at the background is that integrated thematic learning has not been appropriate. The research was intended to demonstrate increased results of integrated studies of thematic with the Model problem based learning at country’s fourth grade elementary school 06 Padang Besi Kota Padang. His type of research is a class action study using qualitative and quantitative approaches. The subject in this study is the teacher (researcher) and student of 28. Research is conducted in two cycles. The Results of cycle research on RPP 76,79% (B), increased from cycles to 92.85% (SB). Cycle 2 at teacher of the activity averages 80.35% (B), increasing in cycle 2 to 96.42% (SB). Implementation of the 2 cycle on student's average 76.79% (b), increased in 2 cycle to 96.42% (sb). Students' study results, on the I average cycle 60,34 (C), increased in 2 cycle to 88.85 (B). So it can be concluded that the model of the problem based based according to (PBL) can increase student teaching results Integrated tennis lessons in elementary school,